Directing And Coordinating (Taujih Wa Tansiq) In Hadith Perspective - MUH. Shofwan Mawally Nafis Badriis; Hikmatul Fauziyah; Siti Isnaeni Wahyuni (Indikator Pendidikan Indonesia, 2022)
This paper aims to find the concepts of directing and coordinating in the hadith perspective, using a qualitative method with a library approach to examine several hadiths and interpreting hadith using the maudhu'I method so as to find new theories related to the directing and coordinating management functions in the hadith perspective.